Design and Synthesis of Novel Thiazolo[5,4-d]pyrimidine Derivatives with High Affinity for Both the Adenosine A1 and A2A Receptors, and Efficacy in Animal Models of Depression - Flavia Varano; Daniela Catarzi; Erica Vigiani; Diego Dal Ben; Michela Buccioni; Gabriella Marucci; Lorenzo Di Cesare Mannelli; Elena Lucarini; Carla Ghelardini; Rosaria Volpini; Vittoria Colotta (MDPI AG, 2021)
New compounds with a 7-amino-2-arylmethyl-thiazolo[5,4-d]pyrimidine structure were synthesized and evaluated in vitro for their affinity and/or potency at the human (h) A1, hA2A, hA2B, and hA3 adenosine receptors (ARs). Several compounds (5, 8-10, 13, 18, 19) were characterized by nanomolar and subnanomolar binding affinities for the hA1 and the hA2A AR, respectively. Results of molecular docking studies supported the in vitro results. The 2-(2-fluorobenzyl)-5-(furan-2yl)-thiazolo[5,4-d]pyrimidin-7-amine derivative 18 (hA1 Ki = 1.9 nM; hA2A Ki = 0.06 nM) was evaluated for its antidepressant-like activity in in vivo studies, the forced swimming test (FST), the tail suspension test (TST), and the sucrose preference test (SPT) in mice, showing an effect comparable to that of the reference amitriptyline.